2023
DOI: 10.3390/biology12091221
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Intracellular Acidity Regulation of Brain Tumor Cells and Consequences for Therapeutic Optimization of Temozolomide

Alaa Tafech,
Pierre Jacquet,
Céline Beaujean
et al.

Abstract: A well-known feature of tumor cells is high glycolytic activity, leading to acidification of the tumor microenvironment through extensive lactate production. This acidosis promotes processes such as metastasis, aggressiveness, and invasiveness, which have been associated with a worse clinical prognosis. Moreover, the function and expression of transporters involved in regulation of intracellular pH might be altered. In this study, the capacity of tumor cells to regulate their intracellular pH when exposed to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 95 publications
0
6
0
Order By: Relevance
“…We validated this methodology by measuring the pH drift observed in the cell culture medium [127]. We then applied it to monitor simultaneously the intra and extracellular pH in two glioma cell lines (murine F98 and human U87 gliomas) that were submitted to a range of acute pH changes from 5.0 to 8.4 [19]. We showed that the two cell lines reacted differently to acidity.…”
Section: (Human Immunodeficiency Virus Type 1) the Results Obtained S...mentioning
confidence: 99%
See 3 more Smart Citations
“…We validated this methodology by measuring the pH drift observed in the cell culture medium [127]. We then applied it to monitor simultaneously the intra and extracellular pH in two glioma cell lines (murine F98 and human U87 gliomas) that were submitted to a range of acute pH changes from 5.0 to 8.4 [19]. We showed that the two cell lines reacted differently to acidity.…”
Section: (Human Immunodeficiency Virus Type 1) the Results Obtained S...mentioning
confidence: 99%
“…While many experiments have investigated cells within their native environments, understanding their intrinsic functioning often requires exposure to controlled conditions outside the norm, for instance, exploring the dynamic capacity of cells to regulate the intracellular pH necessitates subjecting them to a broad range of pH levels, from highly acidic to basic, in a systematic manner. Our research with two glioma cell lines demonstrated the potential to optimize temozolomide efficacy through this approach [19], although it has faced criticism for exposing cells to extreme conditions not typically encountered in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Constitutively increased pHi is an emerging hallmark of cancer that is associated with several cancer cell behaviors (White et al, 2017). While pHi has been shown to increase with metastatic potential in tissue-matched cell lines (Spear and White, 2023), spatial pHi heterogeneity exists in 3D cancer cell cultures (Dovmark et al, 2017; Tafech et al, 2023). Concurrent work in our lab has revealed that microenvironment can alter pHi and concomitantly modulate β-catenin abundance in cancer cell models.…”
Section: Discussionmentioning
confidence: 99%